EKSPRESI BENTUK GEOMETRIS MELALUI PENGGARAPAN TEKSTIL TAPESTRI - Miftahun Naufa (Universitas Andalas, 2018)
Expression of Balance Geometric Shapes In Tapestri is a work of art that describes the balance of form through the arrangement of geometric shapes worked with tapestry techniques. With the shape, line and angle of the geometric that is fixed, straight, firm and regular becomes a character of a distinctive shape. The value and meaning of this geometric work can be seen through the arrangement of geometric shapes created, the arrangement of the geometric shape will form the symbol of balance. The purpose of this tapestry work is to develop and preserve tapestry textile art, to be better known in the academic community as well as the general public, and to create new forms of expressive order. The work of form balancing on the art of tapestry is through the method of creating three stages of six steps ranging from the exploration of ideas to the idea of becoming materialized by the process of designing the form, the composition of color and object protrusion using the technique of weaving and weaving loom like weaving. This tapestry art works using yarn, cloth, and fiber. These born geometric forms are expected to have meanings and values composed through various forms of composition. The form of tapestry art expression in the creation of this final work with three dimensional embodiments. The expression is poured into this equilibrium work with the meanings contained in a useful human life and as a good symbol or symbol. The eight works embodied in panel form have a physical function as wall decoration.Key Words: geometric, expression and tapestry